TRADITION METHIK PADI TRADITION IN KALIGONDO VILLAGE, KECAMATAN GENTENG - Fidiah Safitri; Velo mena (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2019)
The custom of Metik Padi Subdistrict is a custom that exists in Kaligondo Village, Genteng District, Banyuwangi Regency. This custom has existed since the time of Javanese ancestors, this salvation was held as a form of gratitude by farmers to Allah SWT for their safety in cultivating Agricultural Land and the abundant and avoidable harvests from pests. Likewise with the problems raised in the study also has the following objectives: (1). Knowing the history of the rice metik salvation tradition in Kaligondo Village, Genteng District, (2) Knowing the religious significance and values ​​of the rice metik salvation customs in Kaligondo Village, Genteng District, (3). Knowing the efforts of the traditional Metik salvation of rice and during the globalization era in Kaligondo Village, Genteng District. This study uses qualitative research in the form of case studies. To achieve this goal data is collected by means of observation, interviews, documentation. Snippet technique, data validation, data analysis technique used in this study is interactive analysis. The research was carried out in Kaligondo Village, Genteng Subdistrict, Banyuwangi District. The object of the research was the traditional elders, the people of Kaligondo Village, Genteng Subdistrict. From the findings of the research in the field, it has been shown that the custom of selik metik rice has existed since the time of the ancestors of the Javanese community in the village of Kaligondo. The meaning of this custom is the establishment of harmony in society and as a human liaison between the ancestors and their Lord and will be given salvation in the cultivation of their agricultural land. The custom of this rice metik salvation is also influenced by globalization, it can be seen from the lack of public awarenessSo that it is not crushed by the current of globalization.